2012
DOI: 10.1029/2012jb009465
|View full text |Cite
|
Sign up to set email alerts
|

Space‐geodetic evidence for multiple magma reservoirs and subvolcanic lateral intrusions at Fernandina Volcano, Galápagos Islands

Abstract: Using Interferometric Synthetic Aperture Radar (InSAR) measurements of the surface deformation at Fernandina Volcano, Galápagos (Ecuador), acquired between January 2003 and September 2010, we study the structure and the dynamics of the shallow magmatic system of the volcano. Through the analysis of spatial and temporal variations of the measured line‐of‐sight displacement we identify multiple sources of deformation beneath the summit and the southern flank. At least two sources are considered to represent perm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
105
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(136 citation statements)
references
References 58 publications
(79 reference statements)
13
105
0
Order By: Relevance
“…It is apparent that there is no clear relationship between erupted volume (dense rock equivalent, DRE) and the mass of sulfur gases emitted during an eruption6, creating challenges for reconstructing the magnitudes and climate impacts78 of past eruptions recorded as sulfate spikes in ice cores9 and for predicting the impacts of potential future eruptions. Geochemical and geophysical observations of volcanic eruptions are becoming ever more precise, frequent and spatially resolved101112, yet they are rarely considered in tandem, despite the fundamental link between them.…”
mentioning
confidence: 99%
“…It is apparent that there is no clear relationship between erupted volume (dense rock equivalent, DRE) and the mass of sulfur gases emitted during an eruption6, creating challenges for reconstructing the magnitudes and climate impacts78 of past eruptions recorded as sulfate spikes in ice cores9 and for predicting the impacts of potential future eruptions. Geochemical and geophysical observations of volcanic eruptions are becoming ever more precise, frequent and spatially resolved101112, yet they are rarely considered in tandem, despite the fundamental link between them.…”
mentioning
confidence: 99%
“…However, many recent deformation studies that have been based on in situ measurements at Soufriere Hills Volcano [Elsworth et al, 2008;Foroozan et al, 2010Foroozan et al, , 2011Hautmann et al, 2013;Melnik and Costa, 2014] or InSAR data at Fernandina Volcano [Chadwick et al, 2011], Galapagos Islands [Bagnardi and Amelung, 2012], have revealed that the displacement field can only be satisfactorily interpreted by considering two magma reservoirs that are located on the same magma vertical path but at two different depths. On the other hand, all of the studies that have interpreted deformation data with two magma reservoirs and with connecting conduits or dikes have inverted the displacement fields to infer each source of deformation without taking into account the existing flow dynamics between these sources.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in many cases, the structure of the shallow plumbing system and the dynamic processes in calderas are consistent with the emplacement of sill-like magma intrusions (Okada, 1985;Amoruso et al, 2007;Onizawa et al, 2007;Jónsson, 2009;Chang et al, 2010;Woo and Kilburn, 2010;Chadwick et al, 2011;Maccaferri et al, 2011;Menand, 2011;Unglert et al, 2011;Bagnardi and Amelung, 2012;Manconi and Casu, 2012;Bagnardi et al, 2013;Corbi et al, 2015;D'Auria et al, 2015a;Richardson et al, 2015;Rivalta et al, 2015;Trasatti et al, 2015;Le Mével et al, 2016). Usually the intrusion of a sill is modeled as a pressure increase in a horizontal crack (e.g., Fialko et al, 2001;Woo and Kilburn, 2010) which causes deformations and ground uplift.…”
Section: Introductionmentioning
confidence: 99%